Immunization with plasmids encoding M2 acetylcholine muscarinic receptor epitopes impairs cardiac function in mice and induces autophagy in the myocardium - Karla Consort Ribeiro; Roberto Perez Campelo; Daniela del Rosário Flores Rodrigues; Elisabete C. Mattos; Izaira Trincani Brandão; Célio Lopes da Silva; Eliete Bouskela; Camila Guerra Martinez; Eleonora Kurtenbach (Taylor & Francis Group, 2018)
Autoantibodies against the M2 subtype of muscarinic acetylcholine receptors with functional activities have been found in the sera of patients with dilated cardiomyopathy (DCM), and the second extracellular loop has been established as the predominant epitope. However, it has been shown that the third intracellular loop is recognized by Chagas disease patients with severe cardiac dysfunction. In this work, BALB/c mice were immunized with plasmids encoding these two epitopes, and a control group received the empty plasmid (pcDNA3 vector). Serum from these DNA-immunized animals had elevated and persistent titres of antibodies against respective antigens. Heart echocardiography indicated diminished left ventricular wall thickness and reduced ejection fraction for both epitope-immunized groups, and ergospirometry tests showed a significant decrease in the exercise time and oxygen consumption. Transfer of serum from these immunized mice into naïve recipients induced the same alterations in cardiac structure and function. Furthermore, electron microscopy analysis of donor-immunized animals revealed several ultrastructural alterations suggestive of autophagy and mitophagy, suggesting novel roles for these autoantibodies. Overall, greater functional and structural impairment was observed in the donor and recipient epitope groups, implicating the third intracellular loop epitope in the pathological effects for the first-time. Therefore, the corresponding peptides could be useful for autoimmune DCM diagnosis and targeted therapy.